Comparative efficacy of deep transcranial magnetic stimulation versus repetitive transcranial magnetic stimulation in improving lower extremity motor function in subacute stroke patients - Wang, Chengshuo; Zhang, Linli; Liu, Mingyue; Xiang, Aomeng; Qi, Jingman; Fu, Yanxin; Zhao, Ruoxuan; Xiong, Zheyu; Wu, Liang; Zhang, Qin (Frontiers in Aging Neuroscience, 2025)
BackgroundDeep transcranial magnetic stimulation (dTMS) is more beneficial in activating the leg muscle cortical representation. However, to date, no studies have evaluated the advantages of dTMS compared to repetitive transcranial magnetic stimulation (rTMS) in improving lower extremity motor function in subacute stroke patients. This study aims to compare the efficacy of dTMS and rTMS in treating lower extremity motor dysfunction in subacute stroke patients.MethodsIn this single-blind, randomized controlled trial, fifty subacute stroke patients with lower extremity motor dysfunction were randomized to receive either dTMS or rTMS treatment. Patients’ Fugl-Meyer Assessment of Lower Extremity (FMA-LE), 10 m Maximum Walking Speed (10 m MWS), Berg Balance Scale (BBS), Timed Up and Go Test (TUGT), walking velocity, stride rate, stride length, gait cycle, double support percentage, and Resting Motor Threshold (RMT) were assessed before the intervention and after the 4-week intervention. Treatment effects were compared using two-way repeated-measures ANOVA. Correlations between lower extremity motor function and cortical excitability were analyzed using Pearson correlation analysis.ResultsForty-five patients completed the study (dTMS group: n = 22; rTMS group: n = 23). Two-way repeated measures ANOVA showed significant group × time interaction effects for FMA-LE, 10 m MWS, BBS, TUGT, walking velocity, stride length, gait cycle, and double support percentage. Post hoc analyses revealed both groups improved significantly from baseline in FMA-LE, 10 m MWS, BBS, TUGT, RMT, walking velocity, stride length, and double support percentage. The dTMS group additionally improved stride rate and gait cycle, while the rTMS group did not. Post-intervention, the dTMS group demonstrated significantly greater improvements than rTMS in FMA-LE, 10 m MWS, TUGT, and walking velocity. After 4 weeks, RMT was significantly negatively correlated with FMA-LE, 10 m MWS, BBS, and walking velocity. RMT was positively correlated with TUGT.ConclusionBoth dTMS and rTMS can improve lower extremity motor dysfunction in subacute stroke patients. Compared to rTMS, dTMS may provide more facilitative and accelerative effects to promote FMA-LE, TUGT, 10 m MWS, and walking velocity. Therefore, as an adjunct to conventional rehabilitation therapies, dTMS is a valuable therapeutic option in stroke rehabilitation programs.